A substrate for modular, extensible data-visualization - Matelsky, Jordan K.; Downs, Joseph; Cowley, Hannah P.; Wester, Brock; Gray-Roncal, William (Big data analytics, 2020)
Background As the scope of scientific questions increase and datasets grow larger, the visualization of relevant information correspondingly becomes more difficult and complex. Sharing visualizations amongst collaborators and with the public can be especially onerous, as it is challenging to reconcile software dependencies, data formats, and specific user needs in an easily accessible package. Results We present substrate , a data-visualization framework designed to simplify communication and code reuse across diverse research teams. Our platform provides a simple, powerful, browser-based interface for scientists to rapidly build effective three-dimensional scenes and visualizations. We aim to reduce the limitations of existing systems, which commonly prescribe a limited set of high-level components, that are rarely optimized for arbitrarily large data visualization or for custom data types. Conclusions To further engage the broader scientific community and enable seamless integration with existing scientific workflows, we also present pytri , a Python library that bridges the use of substrate with the ubiquitous scientific computing platform, Jupyter . Our intention is to lower the activation energy required to transition between exploratory data analysis, data visualization, and publication-quality interactive scenes.